Estimation of genetic parameters of egyptian and local maize cultivars under high plant density and late planting in Iraq - Entidhar Rashid Mirza (Journal of Kerbala for Agricultural Sciences, 2026)
The aim of this study was estimating some genetic parameters of introduced genotypes of maize at high plant densities and late planting dates for the fall season of 2023. Four Egyptian Genotypes were used and compared with two local Genotypes (and tested at two planting dates (1st and 10th August) and two plant densities (70 and 90 thousand plants h-1). A randomized complete block design (RCBD) with a split-spilt plot arrangement with four replications was used. The traits of tassling and silking, plant height, ear height, stem diameter, number of leaves, leaf area and its index, ear length, and individual plant yield were studied. The results of the genetic analysis showed that the standard error values ​​were low in all the studied traits and in the two dates and densities. The results also indicated that the values ​​of the coefficient of variation were less than 20% for all the studied traits at the two dates and the two plant densities. The genetic variation values ​​were higher than the environmental variation in most of the traits studied, with the exception of the traits of ear height, leaf area, and ear length at the date of 1th August and the density of 70 thousand plants h-1, and plant height, stem diameter, number of leaves, and leaf area index at the date of 1st August and the density of 90 thousand plants h-1. The diameter of the stem, the leaf area, and its evidence at the date of 10thAugust, and the density of 70,000 plants ha-1, the number of leaves, the leaf area, its evidence, and the ear length at the date of 10thAugust, and the density of 90,000 plants ha-1. The environmental variance values ​​were greater than the genetic variance, and the ratio of the genetic variance to the environmental variance for these traits is less than 1. The values ​​of the phenotypic coefficient of variation were higher than the genetic variation values ​​for all the traits studied at the two planting dates and the two plant densities. The results showed that the highest percentage of heritability in the broad sense in the first date was 86.1% under the density of 70 thousand plants ha- 1 for silking trait and in the second date also it was under the density of 70 thousand plants ha-1 as it reached 97.3% for the same trait.